Proliferation of the Internet economy e-commerce for global adoption, resistance and cultural evolution - Shareef, Mahmud Akhter 1966-; Dwivedi, Yogesh Kumar; Williams, Michael D.; Singh, Nitish 1972- (Information Science Reference, 2009)
Summary: "This book specifically develops theories to understand service quality and quality management practice of EC which is completely a new and innovative effort to formulate perceptions of global consumers" - Provided by publisher
Includes bibliographical references and index
Keywords: Electronic commerce; Electronic commerce -- Technological innovations; Information technology; Internet -- Economic aspects; Informationstechnik; Electronic Commerce; Technische Innovation; Internet; Globalisierung